The intracellular fate and transport mechanism of shape, size and rigidity varied nanocarriers for understanding their oral delivery efficiency. (March 2023) - Li, Xin; Jafari, Seid Mahdi; Zhou, Feibai; Hong, Hui; Jia, Xin; Mei, Xiaohong; Hou, Guohua; Yuan, Yu; Liu, Bin; Chen, Shanan; Gong, Yifu; Yan, Huiling; et al.
Abstract: Nanocarriers have become an effective strategy to overcome epithelial absorption barriers. During the absorption process, the endocytosis mechanisms, cell internalization pathways, and transport efficiency of nanocarriers are greatly impacted by their physical properties. To understand the relationship between physical properties of nanocarriers and their abilities overcoming multiple absorption barriers, nanocarriers with variable physical properties were prepared via self-assembly of hydrolyzed α- lactalbumin peptide fragments. The impacts of size, shape, and rigidity of nanocarriers on epithelial cells endocytosis mechanisms, internalization pathways, transport efficiency, and bioavailability were studied systematically. The results showed that nanospheres were mainly internalized via clathrin-mediated endocytosis, which was then locked in lysosomes and degraded enzymatically in cytoplasm. While macropinocytosis was the primary pathway of nanotubes and transported to the endoplasmic reticulum and Golgi apparatus, resulting in a high drug concentration and sustained release in cytoplasm. Besides, nanotubes can overcome the multi-drug resistance by inhibiting the P-glycoprotein efflux. Furthermore, nanotubes can open intercellular tight-junctions instantaneously and reversibly, which promotes transport into blood circulation. The aqueous solubility of hydrophobic bioactive mangiferin (Mgf) was improved by nanocarriers. Most importantly, the bioavailability of Mgf was the highest for cross-linked short nanotube (CSNT) which outperformed free Mgf and other formulations by in vivo pharmacokinetic studies. Finally, Mgf-loaded CSNT showed an excellent therapeutic efficiency in vivo for the intervention of streptozotocin-induced diabetes. These results indicate that cross-linked α-lactalbumin nanotubes could be an effective nanocarrier delivery system for improving the epithelium cellular absorption and bioavailability of hydrophobic bioactive compounds.